Stem Cell Therapy: A Compassionate Use Program in Perianal Fistula - M. D. Herreros; D. Garcia-Olmo; H. Guadalajara; T. Georgiev-Hristov; L. Brandariz; M. Garcia-Arranz (Stem Cells International)
Aim. To report our experience in a compassionate use program for complex perianal fistula. Methods. Under controlled circumstances and approved by European and Spanish laws, a compassionate use program allows the use of stem cell therapy for patients with nonhealing diseases, mostly complex fistula-in-ano, who do not meet criteria to be included in a clinical trial. Candidates had previously undergone multiple surgical interventions that had failed. The intervention consisted of surgery (with closure of the internal opening or a surgical flap performance), followed by stem cell injection. Three types of cells were used for implant: stromal vascular fraction, autologous expanded adipose-derived, or allogenic adipose-derived stem cells. Healing was evaluated at 6th month follow-up. Outcome was classified as partial response or healing. Relapse was evaluated 1 year later. Maximum follow-up period was 48 months. Results. 45 patients (24 male) were included; the mean age was 45 years, which ranged from 24 to 69 years. Since some of them received repeated doses, 52 cases were considered (42 fistula-in-ano, 7 rectovaginal fistulas, 1 urethrorectal fistula, 1 sacral fistula, and 1 hidradenitis suppurativa). Regarding fistula-in-ano, there were 18 Crohn’s-associated and 24 cryptoglandular. 49 cases (94.2%) showed partial response starting 6.5 weeks of follow-up. 24 cases (46.2%) healed in a mean time of 5.5 months. A year later, all patients cured remained healed. No adverse effects related to stem cell therapy were reported. Conclusion. Stem cells are safe and useful for treating anal fistulae. Healing can be achieved in severe cases.